Chemical constituents from Euphorbia hirta. (October 2015) - Li, En-Tao; Liu, Kuan-Hui; Zang, Ming-Hui; Zhang, Xue-Lan; Jiang, Hai-Qiang; Zhou, Hong-Lei; Wang, De-Yun; Liu, Jia-Guo; Hu, Yuan-Liang; Wu, Yi
Abstract: Thirty-one compounds, including fourteen triterpenoids (1 –14 ), seven coumarins (15 –21 ), four lignans (22 –25 ), and six diterpenes (26 –31 ) were isolated from the aerial part of Euphorbia hirta . The structures were elucidated by spectroscopic methods and by comparison of their reported spectroscopic data. These compounds have shown the chemical relationships between this plant and other species from the genus Euphorbia . Highlights: We studied the chemical constituents of Euphorbia hirta and obtained thirty-one compounds. The structures of compounds were elucidated by spectroscopic methods. Five compounds were firstly isolated from Euphorbia, and seventeen compounds were firstly obtained from this species. The obtained constituents showed relationships among the Euphorbia plants.